Novel role for alpha-2-macroglobulin (A2M) as a disease modifying protein in senile osteoporosis - Boregowda, Siddaraju V.; Haga, Christopher L.; Supper, Valentina M.; Booker, Cori N.; Phinney, Donald G. (Frontiers in Cell and Developmental Biology, 2023)
Introduction: In the rapidly aging U.S. population, age-induced bone loss (senile osteoporosis) represents a major public health concern that is associated with a significant increased risk for low trauma fragility fractures, which are debilitating to patients, cause significant morbidity and mortality, and are costly to treat and manage. While various treatments exist to slow bone loss in osteoporosis patients, these suffer from poor tolerability and label restrictions that limit their overall effectiveness. Over the past decade, skeletal stem/progenitor cells (SSPCs), which are the main precursor of osteoblasts and adipocytes in adult bone marrow (BM), have emerged as important players in osteoporosis. Methods: Age-induced skeletal pathology was quantified in elderly (24-month-old) vs. mature (3-month-old) mice by micro-CT and changes in SSPC abundance in the BM of these mice was quantified by fluorescence-activated cell sorting (FACS). SSPCs from elderly vs. mature mice were also analyzed by RNA-Seq to identify differentially expressed genes (DEGs), and gain and loss-of-function studies were performed in human BM-derived mesenchymal stromal cells (BM-MSCs) to assess A2M function. Results: Elderly mice were shown to exhibit significant age-induced skeletal pathology, which correlated with a significant increase in SSPC abundance in BM. RNA-seq analysis identified alpha-2-macroglobulin (A2M), a pan-protease inhibitor that also binds inflammatory cytokines, as one of the most downregulated transcripts in SSPCs isolated from the BM of elderly vs. mature mice, and silencing of A2M expression in human BM-MSCs induced their proliferation and skewed their lineage bifurcation toward adipogenesis at the expense of osteogenesis thereby recapitulating critical aspects of age-induced stem cell dysfunction. Conclusion: These findings identify A2M as a novel disease modifying protein in osteoporosis, downregulation of which in bone marrow promotes SSPC dysfunction and imbalances in skeletal homeostasis.